Exploring Traditional Games with a Literature Review: How Do They Impact Children’s Motor Skills? - Hasan, Baharuddin; Husein, Muhamad; Islam, Syahrizal (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study examines the impact of traditional games on children’s motor development, as well as to identify the educational values contained therein. Materials and methods. This study uses PRISMA guidelines and uses the PICO method data collection technique. By searching and collecting relevant articles using Google Scholar, PubMed, and Scopus obtained with the help of the ‘Publish or Perish’ application. Results. The results showed that traditional games, such as hadangan, clogs and egrang batok, significantly improved children’s gross and fine motor skills. In addition, games such as gobak sodor and jump rope proved effective in improving coordination and cooperation skills. The study also found that physical activity in traditional games supports children’s cognitive and social development, such as communication skills, co-operation and creativity. Conclusion. In conclusion, traditional games have significant benefits for children’s gross motor, social and cognitive development. Research shows that games such as hadangan clogs, egrang batok, gobak sodor, and jump rope not only improve physical skills and coordination, but also cooperation and communication skills among children. In addition, traditional games contribute to the development of children’s creativity and critical thinking.